Hubungan Lama Menderita DM dan Kepatuhan Diet DM dengan Kejadian Luka Gangren pada Penderita DM Di RSUD Bangkinang - Nadilla , Manisha; Nurman, Muhammad; Syahda, Syukrianti (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
According to data from the World Health Organization (WHO) (2020) it is estimated that diabetes is the seventh leading cause of death. Mortality is doubled in diabetic patients with diabetic foot ulcers (gangrene), it is noted that up to 85% of diabetes-related lower limb amputations are preceded by foot ulcers. The population of this study were all DM patients who received outpatient treatment at the Internal Medicine Polyclinic at the RSUD in July 2022 totaling 652 people. While the sample in this study were some DM patients in the internal medicine polyclinic room of the hospital, namely as many as 87 respondents. The sampling technique used is Simple Random Sampling. The measuring instrument used is a questionnaire. The analysis used is univariate and bivariate, processed using a computerized system. Based on the results of the study showed that, of the 87 respondents who suffered from DM, most of them were at risk of long suffering from DM as many as 53 people (60.9%), non-adherence to the DM diet were 50 people (57.5%) and most of them had gangrene injuries as many as 48 people (55,2%). Based on the statistical test with the chi-square test, the p value (0.05) with a 95% confidence level, then Ho was rejected, which means that there is a significant relationship between the length of suffering from DM and DM dietary compliance with the incidence of gangrene injuries in patients with diabetes mellitus. It is hoped that health workers should provide health education more often about programs in diet therapy for diabetics so that they can better understand that good diet therapy can accelerate the wound healing process